Smartphone imaging spectrometer for egg/meat freshness monitoring. Issue 5 (20th January 2022) - Wang, Tianci; Shen, Fuzhou; Deng, Hancheng; Cai, Fuhong; Chen, Shufen
Abstract : A reliable smartphone imaging spectrometer developed foron-site food freshness testing offers portability, CMOS compatibility, enhanced near-infrared spectrum capture capability and on-the-go (OTG) functionality. Abstract : Data transmission between spectroscopy equipment and mobile terminals is critical to realising hand-held field-level monitoring. Currently, on-the-go (OTG) communication technology is a convenient and efficient method of data transmission for mobile devices. However, few people associate spectroscopy equipment with smartphones through the OTG port. This study developed a portable imaging spectrometer with a spectral resolution of approximately 12 nm in the visible-near-infrared band (400–1000 nm). It can be connected to a smartphone through the USB-OTG port to process the spectral signal through the smartphone's system on a chip (SoC). It also displays real-time spectral images of the food samples through the smartphone's screen. Using a support vector machine (SVM) to classify the spectra of the various experimental samples ( e.g. eggs and pork), the model prediction accuracy rate is approximately 90%. This further proves the reliability of the proposed smartphone imaging spectrometer for monitoring the freshness of food samples onsite.